Culinary world - Karabets, J. (My University, 2013)
This article gives the information about the conception of different cultures, customs, traditions, ways of life and national cuisines. Culinary of each country in unique.
Keywords: culinary; national cuisine; comsumption; кулінарія; національная кухня; споживання; кулинария; национальная кухня; употребление; кафедра іноземних мов професійного спрямування